2020
DOI: 10.3126/nh.v14i1.30610
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of French Bean (Phaseolus vulgaris L.) Varieties for Summer Season Production in the Mid–Hills of Central Region of Nepal

Abstract: The experiment on evaluation of open pollinated genotypes of French bean (Phaseolus vulgaris L) was conducted during the summer season of 2016 and 2017 at HRD, Khumaltar, Lalitpur, Nepal to assess the variability in the genotypes and yield potentiality for commercial production. The experiment was laid out in Randomized Complete Block Design (RCBD) with five replications. The two new genotypes viz. Semi Light Long and Long Green Bean were compared with Trishuli and Four Season. Fresh pod yield and yield attrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 3 publications
(4 reference statements)
0
12
3
Order By: Relevance
“…The variation in harvest duration could be due to genotypes, environmental conditions, or interaction of both. The findings of this research showed the longest harvest duration (29 days) in Four Season which contradicts the findings of Dhakal et al, (2020) who reported the longest harvest duration in Semi Light Long such variation might be due to the difference in the growing season.…”
Section: Nepalese Horticulturecontrasting
confidence: 99%
See 4 more Smart Citations
“…The variation in harvest duration could be due to genotypes, environmental conditions, or interaction of both. The findings of this research showed the longest harvest duration (29 days) in Four Season which contradicts the findings of Dhakal et al, (2020) who reported the longest harvest duration in Semi Light Long such variation might be due to the difference in the growing season.…”
Section: Nepalese Horticulturecontrasting
confidence: 99%
“…The differences in pod length and pod diameter among the genotypes might be due to differences in their genetic makeup. Dhakal et al, (2020); Pandey et al, (2011) also reported similar variations in pod length and pod diameter of different genotypes. Highly significant variation among varieties of bean for single pod weight was reported earlier by Kalauni et al (2019) and Muthal et al, (2018).…”
Section: Nepalese Horticulturementioning
confidence: 75%
See 3 more Smart Citations